Boca Mono, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co., [Trinidad and Tobago], 2011)
The postcard shows Monos Island, which is about 0.8 km (half a mile) off the north western end of Trinidad, in the area known as Bocas del Dragon or Dragon’s mouth which is 19km wide and is a series of four straits namely: Boca Grande; Boca de Navios; Boca de Huevos and Boca de Monos.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Straits--Trinidad and Tobago; Bocas del Dragón